PELAKSANAAN PERJANJIAN SEWA MENYEWA ANTARA PENYEWA DENGAN CV CAHAYA RENTAL MOBIL DI KOTA PEKANBARU - Dayang Putri Ayu; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Car rental agreements are often used by the community to fulfill theirneeds, so that the implementation often creates a problem, where the tenantdefaults on the contents of the lease agreement that has been made by the partythat rents out. So that in the end there was a dispute between the two parties. Thepurpose of this study is to find out the process of implementing the agreement, andto know legal safeguards against car rental companies when tenants default.The research method used is a sociological juridical approach that is amethod or method used in legal research conducted directly to the field(interview). Then the results of the study will be analyzed descriptively bycombining data from the results of literature / literature studies and field studies.Based on the results of the study it can be concluded that first, the leasingagreement process carried out by AutoBridal Rent Car rental is a type of writtenagreement between the two parties and is in accordance with Article 1548 of theCivil Code. Second, when the tenant defaults, the company has made severalRepressive efforts in resolving the defaults made by the tenants. One such effort isthrough non-litigation or deliberation / consensus. It is suggested to thegovernment that the arrangement of the leasing agreement be specifically andclearly regulated regarding legal protection for business actors, so that theinterests of business actors can also be protected. To the public to carefully readin advance about the contents of the agreement before signing it, and to theleasing party it is recommended that in making a written agreement not tooburdensome to the tenants.Keywords: Legal Protection, Agreement, Rent a Car